2006
DOI: 10.1074/jbc.m605143200
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen-induced Liver Injury Is Attenuated in Male Glutamate-cysteine Ligase Transgenic Mice

Abstract: Acetaminophen overdose is a leading cause of drug-related acute liver failure in the United States. Glutathione, a tripeptide antioxidant protects cells against oxidative damage from reactive oxygen species and plays a crucial role in the detoxification of xenobiotics, including acetaminophen. Glutathione is synthesized in a two-step enzymatic reaction. Glutamate-cysteine ligase carries out the rate-limiting and first step in glutathione synthesis. We have generated C57Bl/6 mice that conditionally overexpress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…The free radicals attack the cell membrane, thus leading to destabilization and disintegration of the cell membrane as a result of lipid peroxidation (Shakun and Vysotski, 1982). In the present study,we observed a marked elevation of hepatic TBARS content following paracetamol administration was in consistence with the other reports in paracetamol-intoxicated rats (James et al, 2003;Botta et al, 2006;Sener et al, 2006). Constituents of P.O.…”
Section: Discussionsupporting
confidence: 93%
“…The free radicals attack the cell membrane, thus leading to destabilization and disintegration of the cell membrane as a result of lipid peroxidation (Shakun and Vysotski, 1982). In the present study,we observed a marked elevation of hepatic TBARS content following paracetamol administration was in consistence with the other reports in paracetamol-intoxicated rats (James et al, 2003;Botta et al, 2006;Sener et al, 2006). Constituents of P.O.…”
Section: Discussionsupporting
confidence: 93%
“…Although we did not observe higher basal GSH levels, which is probably attributable to GSH negative feedback regulation of GCLc activity (Franklin et al, 2009), it is possible that increased GCLc expression enhances GSH synthesis in MLK3-KO mice, which might account for the decreased APAP-induced liver injury in Mlk3(Ϫ/Ϫ) mice. It was demonstrated that overexpression of GCLc does not affect basal GSH levels but enhances GSH resynthesis after APAP-induced GSH depletion, thereby attenuating drug-induced liver injury (Botta et al, 2006). GCLc levels are regulated transcriptionally, post-translationally, and through degradation, and additional studies will be required to address the mechanisms through which MLK3 modulates GCLc levels.…”
Section: Mlk3 In Apap-induced Liver Injurymentioning
confidence: 99%
“…1, 2, 5, and 6) also suggested that hepatic GSH levels may be increased through FXR-dependent pathways. Gclm functions as a modifier subunit of the glutamate cysteine ligase, the rate-limiting enzyme in GSH biosynthesis (25), and an increase in Gclm was sufficient to increase hepatic GSH biosynthesis (25,26). Interestingly, it has been proposed that APAP-dependent hepatotoxicity is due, at least in part, to depletion of hepatic GSH levels (27)(28)(29).…”
Section: Fxr Provides Protection From Apap-induced Hepatotoxicitymentioning
confidence: 99%
“…Lee et al when compared with wild-type mice (26). The importance of individual FXR-target genes, or combinations of these genes, in providing hepatoprotection from APAP is beyond the scope of the current investigation because it would require studies on multiple knockout mice.…”
mentioning
confidence: 97%